Effects of Reactive Oxygen Species on Mitochondrial Content and Integrity of Human Anastomotic Colorectal Dehiscence: A Preliminary DNA Study - Lucia Potenza; Cinzia Calcabrini; Roberta De Bellis; Michele Guescini; Umberto Mancini; Luigi Cucchiarini; Gennaro Nappo; Rossana Alloni; Roberto Coppola; Laura Dugo; Marina Dachà (Canadian Journal of Gastroenterology)
BACKGROUND: Anastomotic dehiscence is one of the most severe complications of colorectal surgery. Gaining insight into the molecular mechanisms responsible for the development of anastomotic dehiscence following colorectal surgery is important for the reduction of postoperative complications.